Innovation is a state of mind : simple strategies to be more innovative in everything you do - O'Loghlin, James (John Wiley and Sons Australia, Ltd, 2016)
Everyone says that innovation is important. The problem is that no one tells you how to be innovative. Innovation is a State of Mind sets out a step-by-step guide to creating innovative ideas and putting them into action. You'll learn how to generate more ideas with greater potential, how to grow and evaluate them, test their effectiveness and then implement the ones that are going to improve your business.